Methode zur Messung des Einflusses von Lichtimpulsen auf die visuelle Leistungsfähigkeit - Helmer, Melanie (Spektrum der Lichttechnik, 2021)
Due to its dynamic range, the human eye can adapt to a wide variety of light situations within a very short time. If the dynamic range of the eye is insufficient, glare occurs. There is no suitable objective measurement method to describe the effects on visual performance and its course. This was developed and validated as part of this work.